Differences of Reeda Scale in Wound Incision Abdomen Post Obstetrics / Gynaecology Laparotomy with Topical Virgin Coconut Oil (VCO) and Without Topical Virgin Coconut Oil (VCO) - Wahdini, Nanda Tri; Ferry, Ferdinal; Syukur, Sumaryati (Fakultas Kedokteran Universitas Andalas, 2021)
Introduction : Wounds are defects of normal anatomical structures and functions. Injuries can occur because of physical, chemical, or biological trauma. Wound healing is a complex process involving many cells, cytokines, growth factors, proteases, and extracellular matrix (ECM) that work together to restore the integrity of the injured tissue. Virgin Coconut Oil is an oil saturated with medium-chain fatty acids (MCFA), one of which is lauric acid. Based on our research, VCO has wound healing properties. Research conducted in vivo on rabbits and rats experienced an increase in collagen, fibroblast proliferation, and neovascularization which influenced accelerating wound healing.Objective : This study aims to determine the difference in the mean REEDA scale in abdominal incision wounds after obstetric / gynecology laparotomy with topical VCO and those without topical VCO.Material and methods : This study is an experimental research design with a randomized clinical trial that was conducted on 36 people divided into 2 groups (treatment and control). Post-obstetric / gynecology laparotomy patients were subjected to topical VCO application on the incision wound and the REEDA scale was calculated at 24, 48, and 72 hours post-surgery. Statistical analysis is using the Mann-Whitney test.Results : Age mean of the respondents in the treatment group was 32.28 ± 10.42 years old, while the untreated group was 30.5 ± 6.54 years old. The mean REEDA scale for abdominal incision wounds applied topical VCO at 24 hours was 3.17 ± 1.04, at 48 hours was 2.11 ± 1.08, and at 72 hours was 1.39 ± 0.85. The mean REEDA scale for abdominal incision wounds that were not treated with topical VCO at 24 hours was 3.83 ± 0.99, at 48 hours was 3.11 ± 1.37 and at 72 hours was 2.72 ± 1.41. The findings of the experimental analyses showed that there was no association with the use of topical VCO in surgical wounds on a 24-hour REEDA scale (p>0.05), there was a relationship between the use of topical VCO in surgical wounds on a 48-hour and 72-hour REEDA scale (p<0.05). In the care group, the mean REEDA scale decreased by 33.4 % from 24 to 48 hours and 34.1 % from 48 to 72 hours.Conclusion : There is a relationship with the use of topical VCO in post-abdominal incision wounds post obstetrics/gynaecology laparotomy with REEDA scale 48 hours and 72 hours post-surgery. The mean REEDA scale decreased by over 24 to 48 hours and 48 to 72 hours in the treatment group (who administered topical VCO in postoperative incision wounds).Keywords: VCO, REEDA scale, Wound healing